Allergenic Characterization of Best-Selling Hair Products Marketed to Black Women. Issue 1 (January 2022) - Walker, Chloe J.; Pathoulas, James T.; Flanagan, Kelly E.; Wiss, Isabel Pupo; Senna, Maryanne M.
Abstract : Supplemental digital content is available in the text.